Combining Experiments and Atom Probe Tomography-Informed Simulations on γ′ Precipitation Strengthening in the Polycrystalline Ni-Base Superalloy A718Plus - Kirchmayer, Andreas; Lyu, Hao; Pröbstle, Martin; Houlle, Frederic; Förner, Andreas; Huenert, Daniela; Göken, Mathias; Felfer, Peter; Bitzek, Erik; Neumeier, Steffen (Advanced Engineering Materials, 2020)
The strength of superalloys is strongly influenced by γ′ precipitates, whose size and volume fraction which can be adjusted by heat treatments. According to classical precipitation strengthening models, an increasing precipitate diameter should lead to a transition from weak to strong coupling of the dislocation pairs that form superdislocations in the γ′ phase. We show that long-term annealing of the Ni-base superalloy A718Plus at 670 and 680 °C increases the alloy's strength without significantly changing the grain size and η fraction. To understand the effect of the slight increase in γ′ size, detailed atom probe tomography (APT) was performed. Here, different field evaporation rates of the phases strongly affect the determination of the volume fraction when using the usual isosurface construction. This can be mitigated by considering the number density of atoms inside and outside the γ′ precipitates. Using an approximation of the precipitate shapes and arrangements from the APT data in atomistic simulations revealed that precipitate shearing by both, weakly and strongly coupled dislocations can occur in the same sample due to the wide distribution of precipitate sizes. These results highlight the need for advanced strengthening models that take into account the γ′ size distribution.
CRIS-Team Scopus Importer:2020-06-02
Keywords: atom probe tomography; atomistic simulations; Ni-base superalloys; precipitation strengthening; weak–strong pair coupling